Does Gastric Expansibility Affect Weight Loss Success After Laparoscopic Sleeve Gastrectomy? - UPRAK, TEVFİK KIVILCIM; ERDİM, AYLİN; KARATAŞ, SABRİ ALPER; GÜNAL, ÖMER (My University, 2022)
Reduced excess weight loss (EWL) or regain is a worrying problem after metabolic surgery. Factors attainable from the resected specimen that can predict this outcome are investigated. We retrospectively analyzed 64 patients who had undergone laparoscopic sleeve gastrectomy. We collected demographic data, preoperative gastric emptying measurements, volume, expansion capacity, and 6-dimensional measurements of sleeve gastrectomy specimens. Correlations between EWL, body mass index levels, and gastric specimen measurements related to gastric remnant dimensions were also scrutinized. We found a significant correlation between the gastric specimen and remnant gastric volume, the resection line length in the gastric specimen, and 12th-month EWL%. Antrum expansibility was significantly increased in patients with weight regain. There was also a negative correlation between weight loss and age at postoperative first and third years. Sleeve resection line measurement and resected antrum diameter measurements can be used to predict weight loss, especially in the first year postoperatively.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery